Mitigation of pesticide residue levels in the exposed dermal regions of occupationally exposed farmworkers by use of personal protective equipment - Lari, Summaiya; Vanka, Janardhan; Jee, Babban; Pandiyan, Arun; Yamagani, Praveen; Kumar, Senthil Balakrishnan; Naidu, Mohan; Jonnalagadda, Padmaja (Frontiers in Public Health, 2023)
Unsafe pesticide handling practices with the limited use of personal protective equipment (PPE) by the Indian farming groups lead to an increased risk of exposure to pesticides. Therefore, a community-based follow-up study based on dosimeters, wipes, and hand-wash technique was carried out to evaluate the dermal exposure to pesticides and to analyze the impact of the usage of PPE on minimizing the exposure among the farmworkers of Rangareddy district, Telangana, India. Risk in terms of hazard quotient (HQ), hazard index (HI), and safety analysis as margins of safety was assessed. Farmworkers averaged 18 years of farming experience and showed resistance to adopting good agricultural practices. Ten pesticide residues were detected in concentrations ranging from 0.000 to 246 mg ml−1 in hand-wash, 0.000 to 198.33 ng cm−2 in patch dosimeter, and 0.000 to 1,740 ng cm−2 in wipe samples collected from farmworkers not using PPE. The second phase includes the intervention study results that revealed a significant reduction both in the concentrations and the number of pesticide residues detected in the hand-wash, patch, and wipe samples of the farmworkers who have used the PPE provided to them (p < 0.01). Furthermore, the probabilistic health risk assessment in terms of the HQ values ranged from 0.02 to 1029.82, and HI was >1, suggesting the non-carcinogenic risks associated with dermal exposure to pesticides among them. Additionally, the safety risk assessment in terms of the margin of safety suggests that they follow risky handling practices. The study confirms that farmworkers are exposed to pesticides and emphasizes the significance of using PPE in reducing the risk.